Preparation of nanocrystalline MgNb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Letters, 2005)
A gel was formed when a aqueous solution of Mg(NO3)(2), NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, MgNb2O6 (MN). The formation of MN phase and lattice parameters were determined by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Electron microscopy; magnesium niobate; powders; X-ray diffraction

Investigations on Ru doped ZnO: strain calculations and gas sensing study - Navale, Shalaka C.; Ravi, V.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
Pure and ruthenium (Ru) doped nano-crystalline zinc oxide (ZnO) powders were synthesized by using well-known citrate gel route. Citric acid acts as a chelating agent and thus helps in the formation of nanoparticles. The detailed X-ray diffraction (XRD) studies using Hall equation reveal that in the nanoscale dimensions, incorporation of Ru modulates the lattice strain. It is interesting to note that on Ru doping, the compressive strain present in the undoped ZnO changes into tensile strain. We have tested the response of these specimens individually for reducing gases like H(2), LPG (liquefied petroleum gas), C(2)H(5)OH (ethanol), CO, acetone and oxidizing gases like NO, and Cl(2). Undoped ZnO responses perceptibly to LPG while Ru doped sample highly senses ethanol vapors. This might be due to either change in composition on Ru doping or/and difference between basicity of LPG and C(2)H(5)OH vapors. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Ethanol sensor; LPG sensor; Nanomaterials; ruthenium